A restudy of the Sandbian to Katian (Upper Ordovician) graptolites from the East Qilianshan (Chilianshan), Northwest China. (November 2019) - Chen, Xu; Chen, Zhongyang; Mitchell, Charles E.; Chen, Qing; Zhang, Linna
Abstract: The Upper Ordovician Sandbian to Katian strata from the East Qilianshan (northeastern Tibet Plateau) bear a graptolite fauna of moderately high diversity. Graptolites from the Amplexograptus maxwelli beds to the Appendispinograptus longispinus Biozone (Sa2–Ka4 intervals) proposed herein include 27 species of 13 genera. This important graptolite fauna is first described herein although it was initially reported in 1963. Most of them occur in the A. longispinus Biozone corresponding to the Dicellograptus complexus to Paraorthograptus pacificus biozones of the Wufeng Formation in the Yangtze region. Alulagraptus new genus is established based on the materials from the East Qiqiaogou section. The endemic species, e.g., Alulagraptus ensiformis (Mu and Zhang in Mu et al., 1963), Dicellograptus sinicus Mu and Zhang in Mu et al., 1963, and Climacograptus ? papilio Mu and Zhang in Mu et al., 1963, could indicate that East Qilianshan block was separated from South China. UUID:http://zoobank.org/84ab69a2-0b56-4ec3-912e-730da08ab10a